Safety, Clinical Outcome, and Fracture Rate of Femoropopliteal Stenting Using a 4F Compatible Delivery System. Issue 2 (February 2015) - Sarkadi, H.; Bérczi, V.; Kollár, A.; Kiss, D.; Jakabfi, P.; Végh, E.M.; Nemes, B.; Merkely, B.; Hüttl, K.; Dósa, E.
<x xml:space="preserve">Abstract</x> Objective To determine the safety, clinical outcome, and fracture rate of femoropopliteal interventions using 4F stents. Methods Between January 2010 and December 2011, 112 symptomatic patients were treated by stent implantation. Ten patients were lost to follow up; therefore, 102 patients (62 men; mean age 66.4 ± 10.1 years) were retrospectively analyzed. The indication for femoropopliteal revascularization was severe claudication (Rutherford–Becker score = 3) in 63 (62%) patients and chronic critical limb ischemia (Rutherford–Becker score = 4–6) in 39 (38%). Follow up included palpation of peripheral pulses and measurement of ankle brachial index. In patients with suspected in-stent restenosis duplex ultrasonography was performed. In 2013, patients were asked to return for a fluoroscopic examination of the stents. Results 114 lesions (Trans-Atlantic InterSociety Consensus-C and D, n = 45) were treated with 119 stents (Astron Pulsar, n = 42; Pulsar-18, n = 77). Lesions were long (≥100 mm) in 49 cases and heavily calcified in 35. Stents were long (≥120 mm) in 46 cases. Ten stents were partially overlapped. The technical and clinical success rates were 100%. Two puncture related complications were noted, neither of which required surgical repair. Eleven patients died (myocardial infarction, n = 4; stroke, n = 2; cancer, n = 5) and nine patients underwent major amputation (above knee, n = 4). The primary patency rate was 83% at 6 months and 80% at 12 months. The primary assisted patency rate was 97% at 6 months and 94% at 12 months. The secondary patency rate was 86% at 6 months and 85% at 12 months. The prevalence of fractures was 26% (type III and IV, 10%) after an average follow up of 25 months. Conclusion Femoropopliteal stenting using a 4F compatible delivery system can be accomplished with a low complication rate, acceptable fracture rate, and with similar 12 month patency and revascularization rates as their 6F counterparts.